The Application of Word Formation in Students’ Essay Writing: Morphology - Maria Olga Jelimun (Yayasan Visi Intan Permata, 2024)
The purpose of this study was to determine the most prevalent word formations used by students when writing essays. This study utilized a descriptive qualitative method. Five second-year English department students enrolled in an Academic Writing class at UNIKA St. Paulus Ruteng participated in this study. The information was gathered from the exposition composing task. To analyze the data, the researchers used Miles and Huberman’s model, following several stages, namely data reduction, data presentation, and conclusion drawing. According to the findings, the students used 128 processes that fall under five different kinds of word-formations. Affixation, acronyms, blending, compounding, and clipping are all possible subcategories. The understudies applied less mixing and cutting word-arrangement processes. The application of the word-formation procedure also encountered some difficulties. It was unclear to some students how to form blending and clipping. It is hoped that this study will make a significant contribution to our understanding of word formation. Teaching and learning word-based lexical studies in general and word-formations in particular will benefit from the findings of this study.